VITRECTOMY FOR PERSISTENT MACULAR HOLES FOLLOWING OCRIPLASMIN INJECTION: A Comparative Multicenter Study. Issue 12 (December 2017) - Schumann, Ricarda G.; Wolf, Armin; Hoerauf, Hans; Lommatzsch, Albrecht; Maier, Mathias; Wachtlin, Joachim; Koss, Michael J.; Kreutzer, Thomas; Bertelmann, Thomas; Kazerounian, Sara; Mennel, Stefan; Priglinger, Siegfried G.
Abstract : Purpose: To determine functional and anatomical outcomes of pars plana vitrectomy for persistent full-thickness macular hole (MH) after intravitreal injection of ocriplasmin. Methods: This is a multicenter retrospective interventional study of 37 eyes of 37 patients who underwent pars plana vitrectomy with internal limiting membrane peeling for persistent MH after ocriplasmin treatment between December 2013 and December 2015 and comparison with 35 eyes of 35 patients who were offered ocriplasmin injection but underwent pars plana vitrectomy alone without pharmacologic vitreolysis before surgery. In addition, 24 matched pairs (MH diameter at baseline ±5 µ m) were analyzed. Clinical data such as visual acuity, intraoperative characteristics, and spectral domain optical coherence tomography images were reviewed. Main outcome measures were visual acuity and MH closure rate. Results: After a mean follow-up period of 9 months, postoperative mean visual acuity showed no significant differences between ocriplasmin-treated eyes (logarithm of minimum angle of resolution 0.37 ± 0.26, Snellen 20/47) and eyes without ocriplasmin treatment (logarithm of minimum angle of resolution 0.39 ± 0.25; Snellen 20/49) ( P > 0.9). After ocriplasmin injection, mean MH diameter enlarged from 217 ± 102 µ m to 384 ± 239 µ m ( P < 0.001). Matched-pair analysis revealed no difference in gain of visual acuity between the first visit and the last follow-up ( P = 0.29). Macular hole closure was observed in similar proportion in ocriplasmin-treated eyes (97%) and vitrectomy-only eyes (94%) ( P > 0.5). Conlcusion: Eyes with persistent MH after ocriplasmin injection showed significant visual improvement after pars plana vitrectomy. Matched-pair analysis revealed no statistical differences in functional and anatomical postoperative results comparing with eyes of similar MH diameter that proceeded directly to surgery without ocriplasmin pretreatment. Abstract : In this multicenter retrospective investigation, eyes with similar macular hole diameters at baseline had similar functional and anatomical results after pars plana vitrectomy comparing ocriplasmin-pretreated eyes and eyes that proceeded directly to surgery without ocriplasmin injection.